2019
DOI: 10.1039/c8ra09866b
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite functionalized membranes based on silica nanoparticles cross-linked to electrospun nanofibrous support for arsenic(v) adsorption from contaminated underground water

Abstract: Development of nanocomposite functionalized membranes for the removal of As(v) from contaminated water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Although activated carbon is one of the most commonly used adsorbents for pollutant removal, it is expensive. Al-Ghouti et al (2019) prepared silane-and sulfurmodified roasted date pits and applied these for Hg 2+ removal from water. It was observed that Ag NPs uniformly doped in ordered mesoporous silica can reduce Hg 2+ to Hg, which ultimately reacts with Ag present in the NC, followed by alloy formation (Ganzagh et al, 2016).…”
Section: Mercury Removalmentioning
confidence: 99%
“…Although activated carbon is one of the most commonly used adsorbents for pollutant removal, it is expensive. Al-Ghouti et al (2019) prepared silane-and sulfurmodified roasted date pits and applied these for Hg 2+ removal from water. It was observed that Ag NPs uniformly doped in ordered mesoporous silica can reduce Hg 2+ to Hg, which ultimately reacts with Ag present in the NC, followed by alloy formation (Ganzagh et al, 2016).…”
Section: Mercury Removalmentioning
confidence: 99%
“…They can be also used as pre-concentration steps in analytical processes [25]. Different adsorbents such as metal oxides, activated carbons, resins, impregnated resins [26], metal-organic frameworks (MOFs) [27], nanocomposites and biosorbents have been reported for As removal [11,[28][29][30][31][32][33][34]. Cellulose support modified with grafting of amine groups has been used for the binding of copper and the metal-loaded sorbent was efficiently used for As(V) recovery [35][36][37][38].…”
Section: Synthesis Of Sio 2 @Mo(vi)-hs Sorbentmentioning
confidence: 99%
“…Generally, the edge energy increases with an increase in the oxidation state. 29 Comparing the Sb XANES spectra of the Sb(III)-loaded lter with those of the reference compounds (i.e., KSb(OH) 6 and C 8 H 4 K 2 O 12 Sb 2 were used as references for Sb(V) and Sb(III), respectively), indicated that Sb was present in the valence states of Sb(V) and Sb(III). Fig.…”
Section: Stem and Xps Analysesmentioning
confidence: 99%
“…4,5 As a metalloid element, Sb is located in group 15 (VA) of the periodic table, structurally analogous to arsenic, but much less attention has been given to Sb removal when compared with arsenic. 6,7 Generally, the most common aqueous Sb species are inorganic Sb(OH) 6À and Sb(OH) 3 , 8 and Sb(III) is 10 times more toxic than Sb(V). Because of its negative impact on human life, the World Health Organization has set the permissible amount of total Sb in drinking water at 5 mg L À1 .…”
Section: Introductionmentioning
confidence: 99%